PENANGGULANGAN IJIME DI KALANGAN SISWA DI JEPANG - happy mart ampris (Jurnal Pustaka Nusantara dan Budaya, 2013)
Ijime is a disorder that contain ridicule, persecution, honor killings, or even violence committed by students. In writing this journal, the author uses library research and descriptive analyzes were done by describing the data that author got from any references and then analyze it.In addition, the author also uses sociological theory in this study. Sociological theory is a theory which states that people are individuals who can not be separated from public life. The purpose of this study was to determine how ijime prevention among students in Japan. The results of this study are ijime problems that occur among students in Japan can be overcome through participation some elements, namely: students' own self, the family, especially the parents, the school which includes principals, teachers, and other school community and the role of as well as from the government.